Effects of protected area establishment and cash crop price dynamics on land use transitions 1990–2017 in north-eastern Madagascar. Issue 1 (2nd January 2019) - Llopis, Jorge C.; Harimalala, Paul C.; Bär, Roger; Heinimann, Andreas; Rabemananjara, Zo Hasina; Zaehringer, Julie G.
ABSTRACT: We applied a participatory mapping approach supported by very high-resolution satellite imagery to reconstruct spatially explicit, year-to-year land use transitions in two highly biodiverse, data-scarce forest frontier landscapes in north-eastern Madagascar. We explored these transitions in the light of major continuous trends and discrete events highlighted by local farmers as influencing their land use decisions. Our results suggest that the process of establishing protected areas first reinforced ongoing deforestation, but later led to a significant reduction of forest loss rates. Recent cash crop booms appear to have induced agricultural intensification processes in our study landscapes, while also putting additional pressure on forests, as people may be encouraged to clear forest for cash crop cultivation. These findings are crucial to understanding rapid land use change processes in forest frontier contexts in the humid tropics, and especially to informing natural resource governance and development initiatives in complex mosaic landscapes.